1999
DOI: 10.1038/sj.onc.1202827
|View full text |Cite
|
Sign up to set email alerts
|

An invasion-related complex of cortactin, paxillin and PKCμ associates with invadopodia at sites of extracellular matrix degradation

Abstract: Invasive breast cancer cells have the ability to extend membrane protrusions, invadopodia, into the extracellular matrix (ECM). These structures are associated with sites of active matrix degradation. The amount of matrix degradation associated with the activity of these membrane protrusions has been shown to directly correlate with invasive potential. We demonstrate here that microinjection of polyclonal anti-cortactin antibodies blocks matrix degradation at invadopodia supporting the hypothesis that cortacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
343
0
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(363 citation statements)
references
References 35 publications
16
343
0
3
Order By: Relevance
“…Additionally, recent studies have shown the overexpression of cortactin in NIH3T3 cells to result in increased cell invasion/migration in vitro (Patel et al, 1998;Huang et al, 1998). Moreover, cortactin takes part in formation and function of invadopodias in (Bowden et al, 1999) supporting the hypothesis of direct involvement of cortactin in metastasis.…”
mentioning
confidence: 73%
“…Additionally, recent studies have shown the overexpression of cortactin in NIH3T3 cells to result in increased cell invasion/migration in vitro (Patel et al, 1998;Huang et al, 1998). Moreover, cortactin takes part in formation and function of invadopodias in (Bowden et al, 1999) supporting the hypothesis of direct involvement of cortactin in metastasis.…”
mentioning
confidence: 73%
“…Invasive tumor cells form actin-rich protrusions, called invadopodia, that degrade and extend into ECMs (Bowden et al, 1999;Onodera et al, 2005;Weaver, 2006;Cortesio et al, 2008). To evaluate the ability of invadopodia formation during in vitro invasion of SaOS-2 cells, Alexa-labeled gelatin (red) was utilized as ECM (see Materials and Methods).…”
Section: Ror2 Has Important Functions In Ecm Degradation and Invadopomentioning
confidence: 99%
“…Fluorescent images were obtained using a laser scanning confocal imaging system (LSM510, Carl Zeiss, Go¨ttingen, Germany). For ECM degradation assay, glass-bottom dishes were coated with gelatin (Type A with 300 Bloom; Sigma) conjugated with Alexa 594 (Invitrogen) (Alexa-gelatin) and then treated with 0.5% glutaraldehyde, as described earlier (Bowden et al, 1999;Onodera et al, 2005). Cells were cultured on these glassbottom dishes in DMEM, fixed and stained with anti-cortactin antibody or Alexa 488-phalloidin.…”
Section: Reporter Assaymentioning
confidence: 99%
“…Fluorescently-labeled gelatin-coated coverslips were prepared as described by Berdeaux et al (2004), as originally described by Bowden et al (1999). In brief, coverslips were coated with Oregon green 488-conjugated gelatin (Chemicon, Temecula, CA), cross-linked 15 min in 0.5% glutaraldehyde in phosphate-buffered saline (PBS), and incubated for 3 min with 5 mg/ml NaBH 4 in PBS.…”
Section: Extracellular Matrix Degradation Assay and Fluorescence Micrmentioning
confidence: 99%
“…They are regulated by various proteins, including the Arp2/3 complex, N-WASp, WAVE1, Cdc42, ASAP1, cortactin, gelsolin, and cofilin (Bowden et al, 1999(Bowden et al, , 2006Baldassarre et al, 2003;Yamaguchi et al, 2005;Artym et al, 2006;Chellaiah, 2006;Bharti et al, 2007;Clark et al, 2007). Podosomes/invadopodia are found in various mammalian cells such as macrophages, osteoclasts and vascular smooth muscle cells (Linder and Aepfelbacher, 2003).…”
Section: Introductionmentioning
confidence: 99%